Dimensionality of teacher judgments on a competency-based report card in elementary school. (June 2020) - Machts, Nils; Zitzmann, Steffen; Möller, Jens
Abstract: Developments concerning report cards have led to a potential shift from reporting traditional grades to reporting multiple competencies within and across subjects. In this study, we analyzed the dimensional structure of the teacher judgments on a competency-based report card on fourth-grade elementary school students ( N = 469). With a methodologically innovative approach of combining exploratory structural equation modeling (ESEM) and confirmatory factor analysis (CFA), we found one learning-oriented and one social-oriented generic subject-unspecific factor of competency judgments and single factors for each included subject. All subject factors showed relatively high correlations with the respective traditional grades. Second-order commonalities further indicated a general factor represented almost perfectly by the learning-oriented generic judgments. Our analyses generally justified the use of competency-based report cards in terms of the dimensional structure and the association with traditional grades. Further, generic subject-unspecific competency judgments contribute to disentangling the multidimensionality of teacher judgments. Highlights: ESEM and CFA are combined for the analysis of a competency-based report card. Generic judgments differentiate learning-oriented and social-oriented competencies. Competency judgments are highly associated with respective traditional grades. Learning-oriented competencies are highly representative of a general factor. Social-oriented competencies are correlated moderately with subject judgments.